Neoadjuvant therapy in breast cancer - Campone, Mario; Frenel, Jean-Sébastien (Clinical insights (London, England), 2014)
In this seven-chapter book, experts explore current options in the neoadjuvant setting, evaluation of response to treatment, principal goals for neoadjuvant systemic therapy and development of new targeted agents.